Kinerja Riset Universitas, Reputasi Universitas, dan Pilihan Universitas: Sebuah Telaah Sistematis - Alexander Joseph Ibnu Wibowo (Jurnal Manajemen Maranatha, 2014)
Nowadays competition among universities in attracting new students is getting tougher. One aspect that is considered to attract new students is university reputation. This study aims to examine the relationship between university reputation, university research performance, and university choice theoretically. We conduct an exploratory research design through a literature review to answer the research objective in this study. Based on the literature review, we found thatvarious studies have found the influence of university research performance on academic reputation. Similarly, the academic reputation was found to have a significant effect on the university choice. Various studies suggest that researchperformance can be measured by several variables, such as research excellence, scientific research ability, research productivity, strategic alliances through collaborative research, research quality, responsible scientific behavior, and salaryfor scientific productivity. Likewise, the academic reputation can be measured by program-level reputation, institutional-level reputation, and academic performance. Valuable contribution of this study is a theoretical model of university reputation. Itis expected that this study can be followed up with a variety of quantitative empirical studies to ensure the accuracy of this theoretical model.Keywords: Research Performance, University Reputation, University Choice, Marketing, Higher Education.